(untitled) (International Research Journal of Pharmacy, 2022)
Background: Prophylactic uterotonics is the primary preventive measure for PPH, or postpartum hemorrhage, a major cause of maternal death that is mostly linked to uterine atony. As a first-line medication, oxytocin is typically associated with significant hemodynamic instability. Another medication with similar efficacy and superior hemodynamic stability is carbetocin, a long-acting oxytocin analog. Aim: The goal of this study was to compare the hemodynamic effects of carbetocin and oxytocin in patients undergoing elective cesarean sections or LSCS under spinal anesthesia. Methods: In the current study, 140 participants undergoing elective caesarean sections at the Institute under spinal anesthesia during the specified study period were evaluated. They were randomly assigned to two groups, Group I receiving a single intravenous dose of carbetocin and Group II receiving oxytocin. Heart rate, diastolic and systolic blood pressure, side effects, predicted postoperative blood loss, and the need for extra uterotonics were all monitored at regular intervals.